2017
DOI: 10.1515/jccm-2017-0011
|View full text |Cite
|
Sign up to set email alerts
|

Review. Anticoagulant Therapy in Sepsis. The Importance of Timing

Abstract: Sepsis associated coagulopathy is due to the inflammation-induced activation of coagulation pathways concomitant with dysfunction of anticoagulant and fibrinolytic systems, leading to different degrees of haemostasis dysregulation. This response is initially beneficial, contributing to antimicrobial defence, but when control is lost coagulation activation leads to widespread microvascular thrombosis and subsequent organ failure. Large clinical trials of sepsis-related anticoagulant therapies failed to show sur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
12
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(15 citation statements)
references
References 67 publications
0
12
0
1
Order By: Relevance
“…Clinical trials of anticoagulants to treat sepsis-induced coagulopathy have delivered inconsistent results, however an emerging theme is that early coagulation is host protective while late coagulation drives pathology [13]. Subsequently, administration of anticoagulants at early stage can be detrimental to the clearance of pathogen by the native immune system [14]. Additionally, there is little evidence on the beneficial effect of anticoagulants on the overall population, however, is beneficial for critically ill subgroups such as sepsis-induced disseminated intravascular coagulation [13, 15].…”
Section: Discussionmentioning
confidence: 99%
“…Clinical trials of anticoagulants to treat sepsis-induced coagulopathy have delivered inconsistent results, however an emerging theme is that early coagulation is host protective while late coagulation drives pathology [13]. Subsequently, administration of anticoagulants at early stage can be detrimental to the clearance of pathogen by the native immune system [14]. Additionally, there is little evidence on the beneficial effect of anticoagulants on the overall population, however, is beneficial for critically ill subgroups such as sepsis-induced disseminated intravascular coagulation [13, 15].…”
Section: Discussionmentioning
confidence: 99%
“…Acute respiratory distress syndrome (ARDS), acute kidney injury, sepsis, shock, acute liver injury, and acute cardiac injury were defined according to the interim guidance of WHO for SARS-CoV-2 7 . All patients received standard intensive medical treatment in the ICU.…”
Section: Diagnosis and Principles Of Managementmentioning
confidence: 99%
“…Sepsis-induced coagulopathy (SIC) is initially triggered by the combination of procoagulant upregulation, endogenous anticoagulant downregulation, and fibrinolytic impairment. These mechanisms are beneficial host responses that contribute to a hypercoagulable state, which is termed "immunothrombosis"-a defense against the spread of pathogens into the nearby tissues or systemic circulation at an early stage of sepsis (1)(2)(3). However, its dysregulation leads to overwhelming activation of coagulation that induces microthrombosis, particularly disseminated intravascular coagulation (DIC) and multiple organ dysfunction syndrome (MODS).…”
Section: Introductionmentioning
confidence: 99%
“…However, its dysregulation leads to overwhelming activation of coagulation that induces microthrombosis, particularly disseminated intravascular coagulation (DIC) and multiple organ dysfunction syndrome (MODS). The ongoing excessive consumption of coagulation factors ultimately results in a hypocoagulable state with a high risk of severe hemorrhagic complications (2,4,5). Previous studies have reported that the early phase of sepsis is characterized by hypercoagulability, whereas the later stages (severe sepsis or septic shock) trend toward hypocoagulability and are associated with increased morbidity and mortality (1,(6)(7)(8)(9)(10)(11)(12).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation